Elemental Analysis, Extraction Conditions, and Brine Shrimp Toxicity Of Defatted Hylocereus Polyrhizus Seed - Siti Salwa Abd Gani; Siti Atikah Zulkifli; Uswatun Hasanah Zaidan; Azizah Misran; Salina Mat Radzi (MALAYSIAN JOURNAL OF CHEMISTRY, 2024)
Indexed by Scopus